Hormone-Related Cancer and Autoimmune Diseases: A Complex Interplay to be Discovered - Losada-García, A; Cortés-Ramírez, SA; Cruz-Burgos, M; Morales-Pacheco, M; Cruz-Hernández, Carlos D; Gonzalez-Covarrubias, Vanessa; Perez-Plascencia, Carlos; Cerbón, MA; Rodríguez-Dorantes, M (Frontiers in Genetics, 2022)
Neoplasic transformation is a continuous process that occurs in the body. Even before clinical signs, the immune system is capable of recognizing these aberrant cells and reacting to suppress them. However, transformed cells acquire the ability to evade innate and adaptive immune defenses through the secretion of molecules that inhibit immune effector functions, resulting in tumor progression. Hormones have the ability to modulate the immune system and are involved in the pathogenesis of autoimmune diseases, and cancer. Hormones can control both the innate and adaptive immune systems in men and women. For example androgens reduce immunity through modulating the production of pro-inflammatory and anti-inflammatory mediators. Women are more prone than men to suffer from autoimmune diseases such as systemic lupus erythematosus, psoriasis and others. This is linked to female hormones modulating the immune system. Patients with autoimmune diseases consistently have an increased risk of cancer, either as a result of underlying immune system dysregulation or as a side effect of pharmaceutical treatments. Epidemiological data on cancer incidence emphasize the link between the immune system and cancer. We outline and illustrate the occurrence of hormone-related cancer and its relationship to the immune system or autoimmune diseases in this review. It is obvious that some observations are contentious and require explanation of molecular mechanisms and validation. As a result, future research should clarify the molecular pathways involved, including any causal relationships, in order to eventually allocate information that will aid in the treatment of hormone-sensitive cancer and autoimmune illness.